Answer:
10
Step-by-step explanation:
f(-3)=-2(-3)+4=6+4=10
Answer:
23x = -115
Step-by-step explanation:
In the substitution method, you must solve for 1 variable in 1 equation to replace it in the other equation. For the system:
2x - 7y = 4
3x + y = -17
Solving for y in the second equation:
y = -17 - 3x
Replacing y in the first equation:
2x - 7(-17 - 3x) = 4
2x + 119 + 21x = 4
23x = -115
This is the new equation after use the substitution method.
Answer is C.
All real numbers
hope it helps
60%
I pretty sure this is right
3.15 will be your answer i am very sure of that